2016
DOI: 10.1186/s13561-016-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences in allergy immunotherapy (AIT) in Germany – a discrete-choice-experiment

Abstract: BackgroundAllergic Rhinitis (AR) is a common disorder in Europe with Allergic Asthma (AA) as a frequent comorbidity. Allergy immunotherapy (AIT) is the only causal therapy of AR and AA, and can be administered as subcutaneous injections at the physician or as sublingual drops or tablets at home. The usual treatment duration is 3 years.ObjectiveThis study aimed to elicit patient preferences to identify the AIT administration mode preferred by patients.MethodsA discrete-choice-experiment (DCE) was developed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 21 publications
0
25
5
2
Order By: Relevance
“…This is also supported by a patient preference study conducted in Germany using a discrete choice experiment in 239 adults with moderate to severe grass, birch, and/or house dust mite AR. The study found that the attribute most preferred by patients regarding the mode of AIT administration was related to the number and duration of physician visits, with a strong preference for fewer visits with shorter durations [31]. A parallel physician patient survey found that Canadian patients, when asked about their preference for AIT options, were more likely to follow their allergists' recommendation for initiation of SLIT compared with SCIT [32].…”
Section: Discussionmentioning
confidence: 98%
“…This is also supported by a patient preference study conducted in Germany using a discrete choice experiment in 239 adults with moderate to severe grass, birch, and/or house dust mite AR. The study found that the attribute most preferred by patients regarding the mode of AIT administration was related to the number and duration of physician visits, with a strong preference for fewer visits with shorter durations [31]. A parallel physician patient survey found that Canadian patients, when asked about their preference for AIT options, were more likely to follow their allergists' recommendation for initiation of SLIT compared with SCIT [32].…”
Section: Discussionmentioning
confidence: 98%
“…At-home administration of SLIT-tablet can be particularly advantageous in rural communities, where large distances from the nearest clinic may pose additional barriers to access and, with a high number of visits required for SCIT, potentially reducing the likeliness of patients to continue this therapy. A patient preference study conducted in Germany using a discrete choice experiment in 239 adults with moderate to severe grass, birch, and/or HDM AR found that the attribute most preferred by patients regarding the mode of AIT administration was the number and duration of physician visits, with a strong preference for fewer visits with shorter duration [25].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal maintenance dose is reached safely and effectively by up-dosing over several weeks [6]. The convenience and practicability of SCIT, as perceived by patients and physicians, depend largely on the number of injections needed for up-dosing [7]. Short up-dosing has previously been reported to be safe [8][9][10].…”
mentioning
confidence: 99%